2021
DOI: 10.4322/acr.2021.260
|View full text |Cite
|
Sign up to set email alerts
|

Tubular colonic duplication in an adult patient with long-standing history of constipation and tenesmus

Abstract: Background: Intestinal duplications are rare congenital developmental anomalies with an incidence of 0.005-0.025% of births. They are usually identified before 2 years of age and commonly affect the foregut or mid-/hindgut. However, it is very uncommon for these anomalies, to arise in the colon or present during adulthood. Case presentation: Herein, we present a case of a 28-year-old woman with a long-standing history of constipation, tenesmus, and rectal prolapse. Colonoscopy results were normal. An abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This percentage is highest in colorectal duplication than in duplication along other parts of the gastrointestinal tract. Studies have suggested that the duplicated epithelium carries a high risk of carcinogenesis [ 7 , 8 ]. Fecal matter moves more slowly through a duplicated segment, which explains the common symptoms of chronic constipation and delayed transit time.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage is highest in colorectal duplication than in duplication along other parts of the gastrointestinal tract. Studies have suggested that the duplicated epithelium carries a high risk of carcinogenesis [ 7 , 8 ]. Fecal matter moves more slowly through a duplicated segment, which explains the common symptoms of chronic constipation and delayed transit time.…”
Section: Discussionmentioning
confidence: 99%